Investigation of selected foods added with fenugreek that controls postprandial blood glucose in healthy volunteers - Robert, Sathyasurya Daniel (2018)
Increasing evidence suggests that functional foods may benefit those with chronic diseases such as diabetes, obesity, cardiovascular disease and cancer. Preliminary animal and human trials suggest possible hypoglycemic properties of fenugreek when taken orally. The purpose of this study was to determine the chemical composition of fenugreek, to investigate the effects of fenugreek on postprandial plasma glucose (PPG) and satiety among overweight and obese individuals. Galactomannan content of the test foods and the ability of fenugreek seed in reducing glycemic response and glycemic index (GI) when added into buns and flatbreads were also investigated. During the first phase of this randomized controlled crossover trial, 14 overweight or obese subjects were studied in the morning after overnight fasts on four separate occasions. Glycemic responses elicited by 50 g carbohydrate portions of white bread and jam with or without 5.5 g of fenugreek and fried rice with or without 5.5 g fenugreek were determined over 2 h. The main endpoint was the incremental area under the plasma glucose response curve (IAUC). In the second phase of this study 10 healthy human subjects (5 men, 5 women) were given 50 g glucose (reference food, twice); buns (0% and 10% fenugreek seed powder); and flatbreads (0% and 10% fenugreek seed powder) on 6 different occasions. Finger prick capillary blood samples were collected at 0, 15, 30, 45, 60, 90, and 120 minutes after the start of the meal. The palatability of the test meals were scored using Likert scales. Results revealed that fenugreek seed powder contained considerable levels of protein (32.5%), carbohydrate (46.4%), total dietary fibre (TDF) (39.6%), soluble dietary fibre (SDF) (23.8%) and insoluble dietary fibre (IDF) (15.8%). Adding fenugreek to both foods significantly reduced the IAUC compared to the food alone: white bread and jam, 180±22 versus 271±23 mmol × min/L (P=0.001); fried rice, 176±20 versus 249±25mmol × min/L (P=0.001). Fenugreek also significantly reduced the area under the satiety curve for white bread with jam (134±27 versus 232±33mm × hr, P=0.01) and fried rice (280±37 versus 379±36mm× hr, P=0.01). On the other hand, the incremental areas under the glucose curve value (IAUC) of buns and flatbreads with 10% fenugreek (138±17 mmol x min/L; 121±16 mmol x min/L) were significantly lower than those of 0% fenugreek bun and flatbreads (227±15 mmol x min/L; 174±14 mmol x min/L, P= < 0.01). Addition of 10% fenugreek seed powder reduced the GI of buns from 82±5 to 51±7 (P<0.01) and to the GI of flatbread from 63±4 to 43±5 (P<0.01). Furthermore the galactomannan content of fenugreek added flatbreads and buns were 1.54±0.02% and 3.06±0.03 % respectively. It is concluded that fenugreek significantly decreased the PPG response and increased satiety among overweight and obese individuals. In addition, this study demonstrated that by replacing 10% of refined wheat flour with fenugreek seed powder significantly reduces the glycemic response and the GI of buns and flatbreads.